Estrutura e variação florística da comunidade arbórea-arbustiva de uma floresta ciliar do Córrego dos Bois, parque estadual Lapa Grande, Montes Claros/MG - Maria Clara Oliveira Durães (2011)
The objective of this study is to describe the structure and the floristic variation seeking to characterize the spatial distribution arboreal-shrub community and understand how the floristic variation is organized in a fragment of Ciliary Forest of the Córrego dos Bois, Lapa Grande State Park, Montes Claros / MG. To survey of the flora were used 100 plots of 100 m² and sampled arboreal-shrub individuals with DBH 10 cm. In the analysis we calculated the structural parameters of density, dominance, frequency and importance value index (IVI). In total were sampled 764 individuals, belonging to 81 species and 31 families. Fabaceae reached the highest abundance of individuals (183) and species richness (20), mainly by include Anadenanthera colubrina as the third species of higher VI. Next, Anacardiaceae, Salicaceae and Meliaceae are among the families who have achieved notable relevance in this community, due the contribution of Myracrodruon urundeuva, Casearia sp2 and Cedrela fissilis, respectively, among the species with the highest value of importance. The Shannon diversity index was 3.61 nat.ind.-1 and the Pielou equability was 0.82. The floristic variation was verified by main component analysis (MCA), and presented in the eigenvalues of the first two axes that together explained 25.51% of the global variation of the data, being that the axis 1 of PCA presented correlation with the floristic variation towards the nascent-outfall of the Corrego dos Bois and the axis 2 suggests a correlation with the floristic variation towards margin of the interior-river of the forest. The floristic distribution of Myracrodruon urundeuva and Cedrela fissilis is organized toward outfall of the Corrego dos Bois. Anadenanthera colubrina and Casearia sp2, have organization in toward nascent and toward the margin of the river and interior of the forest, respectively. The organization, distribution and pattern of richness of species of arboreal-shrub community is related to the historic of disturbance, interference of the surrounding vegetation and can still be attributed to conditions of high environmental heterogeneity where individuals are established.